Natural rubber/poly (ethylene‐co‐vinylacetate)‐blend‐based nanocomposites - Sharif, Jamaliah; Wan Yunus, Wan Md Zin; Dahlan, Khairulzaman; Ahmad, Mansor (Wiley Periodicals Inc., 2006)
Natural rubber (NR)/poly(ethylene-co-vinyl acetate) (EVA) blend–clay nanocomposites were prepared and characterized. The blend nanocomposites were prepared through the melt mixing of NR/EVA in a ratio of 40/60 with various amounts of organoclay with an internal mixer followed by compression molding. X-ray diffraction patterns revealed that the nanocomposites formed were intercalated. The formation of the intercalated nanocomposites was also indicated by transmission electron microscopy. Scanning electron microscopy, used to study the fractured surface morphology, showed that the distribution of the organoclay in the polymer matrix was homogeneous. The tensile modulus of the nanocomposites increased with an increase in the organoclay content. However, an increase in the organoclay content up to 5 phr did not affect the tensile strength, but the organoclay reduced this property when it was increased further. This study also indicated that a low silicate content dispersed in the blend matrix was capable of increasing the storage modulus of the material. The addition of the organoclay also increased the decomposition temperature of the NR/EVA blends. © 2006 Wiley Periodicals, Inc. J Appl Polym Sci 100: 353–362, 2006